A DNA logic gate with dual-anchored proximity aptamers for the accurate identification of circulating tumor cells. Issue 51 (21st May 2020) - Chen, Tianshu; Fu, Xin; Zhang, Qianqian; Mao, Dongsheng; Song, Yuchen; Feng, Chang; Zhu, Xiaoli
Abstract : A DNA logic gate that integrate the recognition of multiple biomarkers with signal amplification was fabricated to achieve the accurate and sensitive analysis of circulating tumor cells (CTCs). Abstract : We have designed a DNA logic gate that can integrate the recognition of multiple biomarkers with signal amplification to perform the accurate and sensitive analysis of circulating tumor cells (CTCs). It also has the potential to analyze rare cells that exist in small amounts but are of great significance (such as stem cells) in the fields of clinical diagnosis and biomedicine.